2021
DOI: 10.22454/fammed.2021.383659
|View full text |Cite
|
Sign up to set email alerts
|

Sailing the 7C’s: Starfield Revisited as a Foundation of Family Medicine Residency Redesign

Abstract: Amidst a pandemic that has acutely highlighted longstanding failings of the US health care system and the graduate medical education (GME) enterprise that serves it, educators prepare to embark on another revision of the program requirements for family medicine GME. We propose in this article a conceptual framework to guide this endeavor, built on a foundation of the core functions that Barbara Starfield suggested might explain primary care’s salutary effects. We first revisit these “4C’s”—first Contact, Conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Health systems with stronger primary care have better population health outcomes, and evidence indicates this is likely facilitated by a core set of mechanisms commonly termed "the Four C's": first contact, continuity, comprehensiveness, and coordination. 33 Models of care, or the way in which health services are organized and delivered, are important for realizing these "Four C's". Although there is limited research available, this Brief discusses how patient enrolment models (PEMs) that formally attach patients to a regular source of primary care, patient attachment to team-based models of care, and inter-physician practice variations, have been important determinants of access, continuity, and outcomes throughout the COVID-19 pandemic, with implications for primary care capacity moving forward.…”
Section: In What Ways Can Different Models Of Primary Care Support Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Health systems with stronger primary care have better population health outcomes, and evidence indicates this is likely facilitated by a core set of mechanisms commonly termed "the Four C's": first contact, continuity, comprehensiveness, and coordination. 33 Models of care, or the way in which health services are organized and delivered, are important for realizing these "Four C's". Although there is limited research available, this Brief discusses how patient enrolment models (PEMs) that formally attach patients to a regular source of primary care, patient attachment to team-based models of care, and inter-physician practice variations, have been important determinants of access, continuity, and outcomes throughout the COVID-19 pandemic, with implications for primary care capacity moving forward.…”
Section: In What Ways Can Different Models Of Primary Care Support Pa...mentioning
confidence: 99%
“…53 The mechanism is likely the enhancement of the "comprehensiveness" described in the "four C's". 33 Prior to the pandemic, these benefits were contested in some Ontario models. While an early evaluation of team-based care (the FHT model) suggested few benefits, 54 a more recent review conducted by a third party for the Ministry of Health found that FHTs improved patient and clinician experience and improved quality of care (better afterhours access, better quality, and cost neutral).…”
Section: Patient Enrolment Model (Pem) and Continuity Of Carementioning
confidence: 99%
“…[1][2][3] Primary care offers a critical entry point into both COVID-19-and non-COVID-19-related care by providing people with the "Four C's" of first contact, continuity, comprehensiveness, and coordination. 4 The international community has therefore repeatedly called for a focus on strengthening primary health care both in general, and in particular to support COVID-19 pandemic response and recovery. [5][6][7][8] In Canada 9 and internationally, [10][11][12][13][14][15] PCCs often support upstream efforts to address health disparities with an equity-lens that considers the social determinants of health.…”
Section: Introductionmentioning
confidence: 99%
“…The new ACGME FM residency requirements double down on the Starfield 4 C's-first contact care, comprehensiveness, continuity, and care coordination-and extend them to the community. 5 We assert that exposure does not equate to competence: a family medicine resident is not competent in the care of children just because she has completed 5 months of rotations! We expect residents to co-create their education and believe that this will attract the best medical students.…”
mentioning
confidence: 99%